Eventually Consistent: Not What You Were Expecting? - GOLAB, WOJCIECH; RAHMAN, MUNTASIR R.; AUYOUNG, ALVIN; KEETON, KIMBERLY; LI, XIAOZHOU (STEVE) (Communications of the ACM, 2014)
The article examines computer memory storage systems. The design and use of distributed key-value systems in client/server computing is examined. Eventually consistent storage systems, which read and write non-overlapping subsets of data to update replicas, are examined. The consistency form linearizability is considered. Methods of quantifying consistency in eventually consistent storage systems, are discussed including empirical measurement, a combination of systems modeling and prediction and passive analysis.